Heterotopic pregnancy with superfetation following ovarian stimulation: A case report - Lilas Channiss; Tala Tahle; Rami Sabouni; Mohammed Jamalih (Elsevier, 2023)
Heterotopic pregnancy (HP) is a rare phenomenon. Despite its rarity, there has been a notable increase in its incidence in recent decades due to the greater use of in vitro fertilization (IVF). However, information about the relation between ovarian stimulation and HP is scarce. We report a case of HP after ovarian stimulation using clomiphene citrate.A 26-year-old pregnant woman presented to the emergency department with mild vaginal bleeding, and abdominal pain. She had a history of pelvic inflammatory disease (PID) and left salpingectomy due to a previous ectopic pregnancy. She had undergone ovarian stimulation with clomiphene citrate three months earlier. Transvaginal ultrasound revealed an eight-week-old ruptured tubal pregnancy with an intrauterine ten-week-old gestational sac confirming superfetation HP. An urgent laparoscopic right salpingectomy was performed and the extrauterine pregnancy was successfully removed with the preservation of the intrauterine embryo. The course of the intrauterine pregnancy was uneventful and the patient gave birth to a healthy boy via cesarean section.Women receiving ovarian stimulation are at an increased risk of developing HP especially when they also have other predisposing factors for HP. Thus, close monitoring using transvaginal ultrasound with extra attention to the adnexa is required for a timely diagnosis and management of HP.